STUDIES ON GENETIC CORRELATION AND PATH COEFFICIENT ANALYSIS OF BLACKGRAM (Vigna mungo [L.] Hepper) GENOTYPES UNDER SALINITY - T. SABESAN, V. A. MOHANLAL, K. SARAVANAN (Journal of Phytology, 2018)
A study was carried out with twenty-one blackgram genotypes in coastal saline low land in three seasons to study the genetic correlation and path coefficient analysis. Eleven seed yield and yield contributing traits were recorded on the genotypes raised in RBD design with two replications. Based on the pooled analysis, plant height, pods per plant and yield per plant recorded high PCV and GCV value. High heritability along with genetic advance as percent of mean observed for days to first flowering, plant height, primary branches, clusters per plant, pods per plant and yield per plant. Genotypic correlation studies revealed that yield per plant had positive significant correlation with plant height, clusters per plant, pods per plant, pod length and seeds per pod. Path coefficient analysis indicated high positive direct effect of pods per plant and pod length on yield per plant in saline condition. The genotype VBG-10010 performed well under saline environment over seasons.